Dentofacial characteristics of patients with hemifacial microsomia. A literature review. - Camacho, Sandra María; Pabón, Angélica María; Hernández, Jesús Alberto (Revista Estomatología, 2014)
The Hemifacial Microsomía is a congenital disorder that commonly occurs in the hard and soft tissues of half of the face with specific characteristics that define its diagnosis, making clear its difference from other similar diseases. The aim of this review is to recognize the clinical features of Hemifacial Microsomía to perform a correct diagnosis. A search was conducted in the databases (Scielo, Medline, Science Direct) with keywords: Hemifacial Microsomía, Soft tissue, Bone tissue). Sixty four papers assesed the differential diagnosis of HFM. The clinician must recognize the association with syndromes to treat the HFM, thus the therapeutic process can change, and establish the severity of the disease in different tissues for future retrieval and treatment plan.